Correlation between index properties and specific energy for rippability assessment - 341988 Yasmin Abdul Rasheed Khan; Mohd. For Mohd. Amin, supervisor; Fakulti Kejuruteraan Awam (2009)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2009